General Attitudes, Intelligibility, and Acceptability: How Philippine English Is Perceived by Filipino-Americans - Leah Gustilo; Francisco Dumanig; Rodney Jubilado (Languages)
Despite the growing acceptance of the varieties of English, standard language ideology continues to cause some to be valorized and denigrated. This paper examines the attitudes of Filipino-Americans within an inner-circle English variety zone towards Philippine English (PhE), focusing on its status, development, lexicon, intelligibility, and acceptability. The study surveyed 113 Filipino-American speakers of American English (AmE) who were familiar with Philippine culture and PhE. Studies show that some first-language English speakers exhibit negative attitudes towards new English varieties. Contrary to this trend, our findings reveal positive attitudes among AmE speakers towards PhE. However, although it is commonly understood, these positive attitudes do not guarantee the full acceptability of PhE. Notably, there is a growing trend towards the acceptability of PhE neologisms, especially in formal and scientific contexts, indicating a shift in previous perceptions. Additionally, the findings of the study highlight that word-formation processes significantly influence the acceptability of new terms across different speech domains, a novel finding that merits further investigation. Acceptability plays a vital role in the dissemination of local expressions and in shaping the status of a language variety. This research may contribute to understanding the evolving dynamics of the acceptability of PhE and its status in local and international contexts. The positive attitudes towards PhE among American English speakers indicate a shift in perceptions. Language teaching can build on this trend by fostering an environment where students are encouraged to appreciate and respect different English varieties. This can be achieved through exposure to diverse linguistic inputs and discussions on language attitudes.